Anti-hyperuricemia Activity of Ethanol Extract of Bajakah Stem (Spatholobus litoralis Haask) on In Vivo Model: Analysis of Uric Acid and Cyclooxygenase-2 Levels - Ilyas Y.Muhammad; Apriyanto; Adriatman Rasak; Nirwati Rusli; Asriullah Jabbar; Ufu Rindang; Fadhliyah Malik (Window of Health : Jurnal Kesehatan, 2026)
Investigation of bajakah (Spatholobus littoralis Hassk), a typical plant of the island of Borneo, as an anti-hyperuricemia and anti-inflammatory agent through the cyclooxygenase-2 (COX-2) inhibition pathway is important to reveal. This is supported by previous research indicating that bajakah has strong anti-inflammatory and antioxidant effects, with a higher flavonoid content. Evidence-based studies were conducted to determine whether the bajakah stem extract can reduce uric acid levels and inhibit COX-2 as an anti-hyperuricemia therapy. This study was conducted in vivo on mice with a hyperuricemia model induced by potassium oxonate. The treatment consisted of a normal control group, a negative control (Na-CMC, 0.5%), a positive control (allopurinol), and a dose-variation group of Bajakah stem ethanol extract at 100, 200, and 300 mg/kg BW. Uric acid levels were determined at hours 1, 2, and 3 by lateral chromatography and COX-2 levels by the sandwich ELISA method. The study results showed that bajakah stem ethanol extract in the 300 mg/kg body weight dose group was effective in reducing uric acid levels at the 3rd hour from 3.60 ± 0.25 mg/dL to 2.33 ± 0.35 mg/dL, with the greatest reduction of 0.33 ± 0.06 mg/dL, equivalent to 92%, and reduced COX-2 levels by 1.14 ± 0.02 ng/mL, which was significantly different from the negative control (p<0.05), and there was a positive correlation between the reduction in uric acid levels and COX-2 inhibition in hyperuricemic animal models. The conclusion of this study is that administration of bajakah wood can increase uric acid levels while simultaneously inhibiting inflammation, making it a potential candidate for development as an antihyperuricemic and anti-inflammatory drug.